VizieR Online Data Catalog: J-type carbon stars in LMC (Morgan+, 2003) - Morgan, D. H.; Cannon, R. D.; Hatzidimitriou, D.; Croke, B. F. W. (2003)
Most of the carbon stars observed with 2dF were selected from the newly completed catalogue of 7760 carbon stars by (Kontizas et al., 2001, Cat. , hereafter KDMK01). (1 data file).
Keywords: Magellanic Clouds; Photometry: infrared; Stars: carbon